Levosimendan, a new calcium-sensitizing inotrope for heart failure - Ng, Tien M H (Pharmacotherapy, 2004)
Calcium sensitizers are a new class of inotropes that share the in vitro properties of calcium sensitization and phosphodiesterase inhibition. Levosimendan is a distinct calcium sensitizer, as it stabilizes the interaction between calcium and troponin C by binding to troponin C in a calcium-dependent manner, improving inotropy without adversely affecting lusitropy. It does not exhibit clinically relevant phosphodiesterase inhibition at therapeutic concentrations. It also exerts vasodilatory effects, possibly through activation of several potassium channels and other less well characterized mechanisms. The pharmacokinetics of levosimendan are similar in healthy subjects and patients with heart failure and remain relatively unaltered by age, sex, and organ dysfunction. In preclinical and clinical studies, levosimendan exerted potent dose-dependent positive inotropic and vasodilatory activity. Unlike conventional inotropes, levosimendan is not associated with significant increases in myocardial oxygen consumption, proarrhythmia, or neurohormonal activation. The most common adverse effects are attributable to the vasodilation. Two large, double-blind, randomized trials demonstrated favorable hemodynamic effects, improved tolerability, and a possible mortality benefit over dobutamine and placebo in patients who had acute symptoms of failure and required inotropic therapy. The long-term effect on patient outcomes is being confirmed in ongoing placebo- and inotrope-controlled trials. Levosimendan appears to be an effective inodilator devoid of the detrimental effects of conventional inotropes. In the future, levosimendan may provide a promising alternative to conventional inotropes for patients with acutely decompensated heart failure.